Atividade celulolítica e proteolítica de bactérias isoladas do trato gastrointestinal e do processo de compostagem dos restos orgânicos de hipopótamo - Ramos, Geomarcia Feitosa da Cruz [UNIFESP] (2013)
The bioprospection for cellulase and protease producers is a promiss strategy for the discovery of potential biocatalysts for use in hydrolysis of ligninocellulosic materials as well as proteic residues. These enzymes can increment and viabilize production of second generation ethanol from different and alternative sources. In this context, the goal of the present study was the investigation about the cellulolytic and proteolytic abilities of bacteria isolated from gastrointestinal tract of a hippopotamus as well as from the composting process of its organic remnants. The bacterial isolates were obtained through the platting of the samples in different culture media and incubation temperatures. After the bacterial isolation, the strains were submitted to qualitative enzymatic assays to investigate their cellulolytic ability according methodology described by Hankin & Angnostakis (1975). Subsequently they were quantitatively evaluated (FPase), following procedures described by Xiao et al. (2004). Proteolytic analyzes were also developed using high throughput screening approach, thorugh the evaluation of fluorescent peptide probes described by Oliveira et al. (2012). As results, in the qualitative assays for cellulolytic ability detection, it was obtained 70 positive hits from 159 isolated bacterial strains. After quantitative analyzes , 44% of these hits were selected, but 7% (5 strains) (FPZSP_CTT 685; FPZSP_CTT 651; FPZSP_CTT 662; FPZSP_CTT 621; FPZSP_CTT 636) showed FPase activity up to 12.8 FPU/mL, which is compatible to the adopted positive control (Trichoderma reesei). In relation to the proteolytic activities, 8 strains presented relative activity above 10%, which superpassed results described by the literature. Molecular analyzes based on the identification of 16S rDNA, together with mass spectrometry results from MALDI-TOF analyzes, could reveal that the majority of the selected bacterial isolates, about their enzymatic abilities, were affiliated to Bacillus genus. In summary, from the obtained results, it could be affirmed that the obtained microflora constituted potential source of interesting biocatalysts for future investigations about its industrial applications, looking for cellulolytic and proteolytic activities.